2017
DOI: 10.32609/0042-8736-2017-9-28-50
|View full text |Cite
|
Sign up to set email alerts
|

Urgency of financial markets’ and non-banking financial sector reform

Abstract: Russian economy slowdown is exhibited by the investment crisis; its termination is a key factor in the resumption of sustainable growth. As the deficit of durable investment resources is acutely felt today, the article demonstrates that the development of the domestic non-banking financial sector can serve as an efficient mechanism for the long-term investment capital formation. The current state of Russian non-banking financial sector is characterized by numerous structural problems so that a special program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Thus, if, earlier (Stolbov 2008) a significant positive relationship between the financial depth of the economy and GDP growth was not found, although it was assumed that, as the financial market developed, it could become a factor in economic growth, then, in later studies, such a relationship was confirmed (Danilov et al 2017).…”
Section: Review Of the Literaturementioning
confidence: 92%
“…Thus, if, earlier (Stolbov 2008) a significant positive relationship between the financial depth of the economy and GDP growth was not found, although it was assumed that, as the financial market developed, it could become a factor in economic growth, then, in later studies, such a relationship was confirmed (Danilov et al 2017).…”
Section: Review Of the Literaturementioning
confidence: 92%
“…В работе Ю. Данилова, О. Буклемишева, А. Абрамова отмечалось, что «…страны с наибольшим разрывом между развитием банковского сектора и небанковского финансового сектора оказываются наиболее уязвимыми перед лицом кризисных явлений на мировом финансовом рынке. Это происходит потому, что банковский сектор является транслятором внешних шоков, в то время как институциональные инвесторы, являющиеся ядром небанковского финансового сектора, напротив, абсорбируют внешние шоки, снижая их воздействие на реальный сектор экономики» [33].…”
Section: особенности предвидения глобальных кризисов д ля россииunclassified